PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA GURU NON PNS DI SMK NEGERI 1 BANYUANYAR PROBOLINGGO - jurnalmap map; Agus Yudiyanto; Mei Indrawati; Chandra Kartika (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
This research was conducted at SMK Negeri 1 Banyuanyar Jln. Klenang Lor No. 100 Banyuanyar Probolinggo Regency. This study aims to analyze the effect of compensation, work motivation, and performance through job satisfaction of Non PNS teachers in SMK Negeri 1 Banyuanyar Probolinggo. The population in this study were all non civil servant teachers of SMK Negeri 1 Bayuanyar Probolinggo, amounting to 33 people. The analytical method of this study uses path analysis. The results showed that compensation had a significant effect on job satisfaction, work motivation had a significant effect on job satisfaction, compensation had a significant effect on performance, motivation had no significant effect on employee performance, job satisfaction significant effect on employee performance, compensation has a significant effect on performance through job satisfaction of non PNS teachers, work motivation has a significant effect on performance through job satisfaction of Non PNS teacher SMK Negeri 1 Banyuanayar Probolinggo. Keywords: compensation, work motivation, job satisfaction and performance.